Towards an Ethical Canon of Postwar Romanian Literature: Monica Lovinescu on Women Writers (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper looks into Romanian critic Monica Lovinescu’s writings in order to identify the criteria she employs for the analysis of Romanian women writers after World War II. Covering mostly fiction and memorialistic literature, Monica Lovinescu played an important role in launching the careers of contemporary women writers, while also revisiting forgotten or marginal texts authored by members of older generations. Her value system brings together aesthetic and ethical frameworks that take into account the larger socio-political context which the writers relate to. Even though the critic’s way of reading is not an explicitly feminist one, her analyses and hermeneutical technique still consider the writer’s gender, especially as she thinks that Romanian women writers were often marginalized by male scholars who dominated the literary field during and after communism.
Keywords: Monica Lovinescu; literary criticism; women writers; ethics; literary value